Implementasi Sistem Informasi Geografis Lokasi Pertambangan Batu Bara Menggunakan Quantum GIS - Triokta Putra Ulil Amri, Nugraha; Kurniabudi, Kurniabudi (LPPM Universitas Dinamika Bangsa, 2024)
Geographic Information System (GIS) is an information system that utilizes geographic data to map, analyze, and manage information in a geographic context. PT. GEA Lestari, a coal mining company, still uses conventional processes in recording and mapping mining locations that are prone to data loss and errors. This study aims to design and implement a web-based GIS using Quantum GIS (QGIS) for the coal mining location at PT. GEA Lestari. The goal of this study is to reduce data loss, improve mining location accuracy, provide better spatial analysis, and provide accurate and up-to-date information to the company's management. The Scrum method is used in software development, and Unified Modeling Language (UML) is used in system design. The resulting system is expected to be more effective and efficient in managing the company's geospatial data and improving decision-making. The GIS is implemented using web mapping technology with the Leaflet framework and PHP programming language.